Real-time slicing algorithm for Stereolithography (STL) CAD model applied in additive manufacturing industry - F. A., Adnan; F. R. M., Romlay; Nasir, Shafiq (IOP Publishing Ltd, 2018)
Owing to the advent of the industrial revolution 4.0, the need for further evaluating processes applied in the additive manufacturing application particularly the computational process for slicing is non-trivial. This paper evaluates a real-time slicing algorithm for slicing an STL formatted computer-aided design (CAD). A line-plane intersection equation was applied to perform the slicing procedure at any given height. The application of this algorithm has found to provide a better computational time regardless the number of facet in the STL model. The performance of this algorithm is evaluated by comparing the results of the computational time for different geometry.